Combination of Symptom Profile, Endoscopic Findings, and Esophageal Mucosal Histopathology Helps to Differentiate Achalasia from Refractory Gastroesophageal Reflux Disease - Chia-Chu Yeh; Chia-Tung Shun; Liang-Wei Tseng; Tsung-Hsien Chiang; Jia-Feng Wu; Hui-Chuan Lee; Chien-Chuan Chen; Hsiu-Po Wang; Ming-Shiang Wu; Ping-Huei Tseng (Diagnostics, 2021)
Achalasia, a rare primary esophageal motility disorder, is often misdiagnosed as refractory gastroesophageal reflux disease (GERD). This study is aimed to identify the clinical and histopathologic features that may help to differentiate these two entities. Patients with untreated achalasia and those with refractory reflux symptoms despite ≥8 weeks of proton-pump inhibitor treatment were enrolled prospectively. All patients underwent validated symptom questionnaires, esophagogastroduodenoscopy with biopsy, and high-resolution impedance manometry (HRIM). Histopathology of esophageal mucosa was compared based on four pre-determined histological criteria: basal cell hyperplasia or papillae elongation, eosinophilic infiltration, petechiae formation, and hypertrophy of the muscularis mucosae (MM). Compared with the GERD patients, patients with achalasia had similar reflux symptoms, but higher Eckardt scores, fewer erosive esophagitis and hiatal hernia, more esophageal food retention on endoscopy, and higher prevalence of hypertrophy of the MM and petechiae formation on histopathology. Multivariate logistic regression based on Eckardt score ≥4, normal esophagogastric junction morphology or esophageal food retention, and coexistence of petechiae formation and hypertrophy of the MM, established the best prediction model for achalasia. Therefore, combination of routinely accessible variables, including Eckardt score, endoscopic features, and histopathology obtained via esophageal mucosal biopsy, may provide an earlier identification of achalasia.